Sequência de ensino investigativo sobre as propriedades térmicas: evidências em modelos mentais e subsunçores - Barbosa, José Bruno dos Santos (2021)
This dissertation deals with a proposal for an Investigative Teaching Sequence (ITS) for the understanding of thermal properties, based on David Ausubel's Theory of Meaningful Learning and Johnson-Laird's Mental Model, seeking to meet the needs for a phenomenological and phenomenological understanding. acquisition of concepts between causalities in the microscopic world and macroscopic perceptions. The application of the ITS was carried out in the classroom (in-person mode) during the COVID-19 pandemic period, so that the presence of students in the classroom alternated, that is, half of the students were present in one day and the another half of the students attended the next day. To assess the ITS, several conceptual tests were developed, such as the pictorial test and an instrument called Test on Understanding Thermal Properties (TUTP) from the selection of relevant items from other tests known in the literature that assess thermal knowledge. Based on the ITS, support material for the teacher was created, an educational product, with all the methodological guidelines for implementation in any school. The results showed that ITS has the potential, they are promising to contribute to learning. There was a significant improvement in the representation of students' mental models, as well as an evolution in the number of correct answers in TUTP, improving the student's profile.